Contribution of tribbles protein family members in glioblastoma cells - Leite, Letícia de Pinho (2023)
Glioblastoma (GBM) is the most lethal and common form of brain tumor. Currently, the standard treatment comprises surgery, radiotherapy, and chemotherapy with temozolomide (TMZ). However, its prognosis is very deficient due to acquired resistance to therapy and frequent tumor recurrence. Despite research advances, GBM remains largely incurable, with an average survival expectation of 15 months. To improve patients’ response to treatment there is an urgent need for new therapeutic strategies. Tribbles family members (TRIB1, TRIB2, and TRIB3) are pseudokinases known to regulate essential processes such as cell survival and proliferation by modulating signaling pathways. The upregulation of Tribbles has been correlated with a poor prognosis in different types of cancer, such as colorectal and breast cancer, although little is known about their role in GBM. Previous studies have linked high levels of Tribbles with the progression of different tumors. Preliminary data from our laboratory identified the correlation of high mRNA levels in GBM, resulting in a worse prognosis. Thus, we hypothesized that Tribbles proteins have a tumorigenic role in GBM. Our project focused on generating cell-based tools that allowed the modulation of Tribbles protein levels on GBM cells. Our results showed that we successfully generated knock-out (KO) GBM lines for TRIB2 and TRIB3. Assays with the generated KO lines demonstrated that inhibition of TRIB3 resulted in decreased proliferation and cell viability in GBM cells. Furthermore, the reduction of TRIB2 levels caused arrest in the mTOR signaling pathway. In general, our results lead to the understanding that Tribbles proteins contribute to the tumorigenesis of GBM cells.